2010
DOI: 10.1186/1477-7819-8-2
|View full text |Cite
|
Sign up to set email alerts
|

Blurred vision due to choroidal metastasis as the first manifestation of lung cancer: A case report

Abstract: BackgroundReduction in visual acuity combined with blurred vision is rarely the first sign of lung cancer and very few cases have been announced globally.Case presentationA case of a 46-year-old man who admitted with blurred vision is presented. His medical history, apart from a mild gastritis under treatment was negative. Ocular examination revealed a decrease in visual acuity due to a choroidal tumor. Further image body scans demonstrated a right lung lesion with dissemination to other organs. Diagnosis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 6 publications
1
25
0
2
Order By: Relevance
“…Choroidal metastasis, which is seen rarely, is most commonly seen in breast and lung cancers. The incidence of ocular metastases of lung cancers has been reported to be 2-7% in the literature [9]. The diagnosis of ocular metastases is based on clinical findings supported by imaging techniques [9].…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal metastasis, which is seen rarely, is most commonly seen in breast and lung cancers. The incidence of ocular metastases of lung cancers has been reported to be 2-7% in the literature [9]. The diagnosis of ocular metastases is based on clinical findings supported by imaging techniques [9].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this unusual site to be target for secondary metastasis from lung cancer is generally unknown. It is, however speculated that is high vascularity may consist a reasonable explanation (1) . The other frequent sites of choroidal metastasis are alimentary tract cancers, prostate, skin melanoma, kidneys, contralateral choroidal melanoma, thyroid and testis (5) .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 22% of patients diagnosed with CM had a concurrent diagnosis of central nervous system metastasis. Differential diagnosis includes primary choroidal melanomas, benign lesions such as hemangioma, and inflammatory granulomas (1) . Systemic chemotherapy can lead to total involution of the CM with improvement of the visual acuity (7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential diagnosis includes primary melanomas, benign lesions such as hemangioma and inflammatory granulomas [11]. The diagnostic investigation of the referred case included the following complementary tests: FAF, FAG, OCT, ocular USG, X-ray, abdominal USG, MRI and lung biopsy through thoracotomy.…”
Section: Discussionmentioning
confidence: 99%